PENGARUH INTENSITAS PENGGUNAAN MEDIA SOSIAL DAN TINGKAT KONFORMITAS KELOMPOK TEMAN SEBAYA TERHADAP TINGKAT PERILAKU CYBERBULLYING - Dewi Larasati; Sunarto . (Interaksi Online, 2020)
Along with the development of the internet, most people from any stage of ages used social media more than ever. As the growth of social media users, the number of cyberbullying cases had also increased. Social media as a disseminator of information that can be reached by all the people in the world had become the main place for cyberbullying. Among all ages, young people are the most engaged in cyberbullying. Not only had done alone, this behavior also had done in group. The purpose of this study is to know how much the influence of intensity of social media use and peer group conformity level towards the level of cyberbullying behavior. This study had been explained by Uses and Gratification Theory by Elihu Katz, Herbert Blumbler dan Jay G. Gurevitch. This study was used probability sampling technique and multistage random sampling. The population in this study was the people of Banjarnegara City who are active user of social media around age 18-24 years old. Data analysis was used simple linear regression for the first and the second hypothesis and multiple linear regression for the third hypothesis. The results of this study show a hypothesis about the positive influence between intensity of social media use towards the level of cyberbullying behavior with 0,448 of coefficients correlations value, the positive influence between peer group conformity level towards the level of cyberbullying behavior with 0,310 of coefficients correlations value, and the positive influence between intensity of social media use and peer group conformity level towards the level of cyberbullying behavior. With a strong enough level of adherence with 5,145 of significance and a large influence on intensity of social media use and peer group conformity level by 21,7% towards the level of cyberbullying behavior.